Periodontal disease in mouth-breathing patients: Literature review (Research, Society and Development, 2022)
Periodontal disease involves pathological processes affecting the periodontium. Mouth breathing parafunction leads to changes in salivary flow patterns and water imbalance, resulting in oral disease. The aim of this study was, through a literature review, to analyze the results of several investigations that have established a relationship between periodontal disease and mouth breathing. Methodology: a search and selection of articles related to periodontal disease in patients with mouth breathing was carried out. The search criteria taken into account were: electronic databases, key words and meeting the indispensable requirement of being less than 5 years old. Thirty-three articles were selected that met the criteria for the present review. Results and conclusion: periodontal disease and mouth breathing may be associated with generalized systemic inflammation. Changes in the nasal breathing pattern may alter normal anatomical structures leading to the development of periodontal disease triggers.